2020
DOI: 10.18632/aging.103195
|View full text |Cite
|
Sign up to set email alerts
|

Apelin enhances IL-1β expression in human synovial fibroblasts by inhibiting miR-144-3p through the PI3K and ERK pathways

Abstract: INTRODUCTION Osteoarthritis (OA) is a multifactorial disease that manifests with synovial inflammation, cartilage destruction, joint swelling and pain [1, 2]. Among the various risk factors, obesity has been linked to the risk of developing OA [3, 4], with the Framingham Heart Study demonstrating a 1.5-to 2-fold higher risk of www.aging-us.com

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 45 publications
1
18
1
Order By: Relevance
“…RNA isolation and RT‐qPCR assays followed the methodology described in our previous study (Chang et al, 2020).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…RNA isolation and RT‐qPCR assays followed the methodology described in our previous study (Chang et al, 2020).…”
Section: Methodsmentioning
confidence: 99%
“…Wt‐IL‐1β and mut‐IL‐1β‐3ʹ‐UTRs were purchased from Invitrogen. Luciferase activity was quantified using the methodology described in our previous studies (Chang et al, 2020; Chen, Lu, et al, 2020).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The major pathological abnormalities in OA include cartilage degeneration, remodeling of subchondral bone, and synovial membrane inflammation (synovitis). Although the degree of inflammation in OA is remarkably less than that in rheumatoid arthritis, synovitis is now considered an important feature of OA that adversely affects whole joint function (21)(22)(23). Evidence-based medicine has demonstrated that acute or chronic synovitis in varying degrees was observed in OA patients (24).…”
Section: Discussionmentioning
confidence: 99%